2015
DOI: 10.1016/j.devcel.2015.01.032
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas9 Vector System for Tissue-Specific Gene Disruption in Zebrafish

Abstract: Summary CRISPR/Cas9 technology of genome editing has greatly facilitated the targeted inactivation of genes in vitro and in vivo in a wide range of organisms. In zebrafish it allows the rapid generation of knock-out lines by simply injecting a guide RNA (gRNA) and Cas9 mRNA into one-cell stage embryos. Here, we report a simple and scalable CRISPR-based vector system for tissue-specific gene inactivation in zebrafish. As proof of principle, we used our vector with the gata1 promoter driving Cas9 expression to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
297
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(307 citation statements)
references
References 31 publications
3
297
0
5
Order By: Relevance
“…S5). This observation reveals that randomly generated in-frame alleles, which potentially maintain open reading frame integrity (yet nonetheless might impact amino acid residues important for protein function), are a major uncontrolled variable in the use of crispants induced by any method to directly assess loss-of-function phenotypes, both on a whole-embryo (Shah et al, 2015; this study) and on a tissue-specific (Ablain et al, 2015;Stolfi et al, 2014) scale.…”
Section: Crispants Replicate Loss-of-function Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…S5). This observation reveals that randomly generated in-frame alleles, which potentially maintain open reading frame integrity (yet nonetheless might impact amino acid residues important for protein function), are a major uncontrolled variable in the use of crispants induced by any method to directly assess loss-of-function phenotypes, both on a whole-embryo (Shah et al, 2015; this study) and on a tissue-specific (Ablain et al, 2015;Stolfi et al, 2014) scale.…”
Section: Crispants Replicate Loss-of-function Phenotypesmentioning
confidence: 99%
“…Somatic and tissue-specific mutagenesis has recently been reported for Ciona embryos (Stolfi et al, 2014), is possible for assessing tumorigenesis in mice (Platt et al, 2014), and is achievable using mosaic transgene injection in zebrafish (Ablain et al, 2015). Reproducible and significant phenotype penetrance and expressivity in a given cell type or on a whole-embryo scale requires a mutagenesis efficiency close to or reaching saturation, ideally by providing a limited number of alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, sgRNA sequences and lengths (31), Cas9 cleavage activity and target preferences (32,33), and the means by which Cas9 and sgRNA(s) are expressed (e.g. transient, constitutive (34), or induced (35,36)), can be altered to control the pace, temporal window and tissue(s) at which the barcodes are mutated. For example, coupling editing to cell cycle progression might enable higher resolution reconstruction of lineage relationships throughout development.…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9 system (Cong et al, 2013;Haurwitz et al, 2010;Mali et al, 2013) has been shown to reliably insert or delete DNA at precise sites within the zebrafish genome (Hwang et al, 2013;Irion et al, 2014). One strategy for tissue-specific genetic manipulation is to control the expression of the Cas9 protein using a known enhancer element (Ablain et al, 2015). Here we created a UAS-driven nuclearlocalized Cas9 that has eGFP-CAAX expression from a 2A peptide to facilitate epithelial cell-type specific loss-of-function studies in the zebrafish (Fig.…”
Section: Uas Lines To Study Cell Biologymentioning
confidence: 99%